Transformation after Lausanne : radical evangelical mission in global-local perspective. - Tizon, Al (Regnum studies in mission., 2008)
Lausanne '74 (the First International Congress on World Evangelization) inspired evangelicals around the world to take seriously the full implications of the gospel for mission. This was especially true of a worldwide network of radical evangelical mission theologians and practitioners, whose post-Lausanne reflections found harbor in the notion of "Mission as Transformation." This missiology integrated evangelism and social concern like no other, and it lifted up theological voices coming from the Two-Thirds World to places of prominence. This book documents the definitive gatherings, theological tensions, and social forces within and beyond evangelicalism that led up to Mission as Transformation. And it does so through a global-local grid that points the way toward greater holistic mission in the twenty-first century